Pengaruh Pelayanan Fiskus, Pengetahuan Perpajakan dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak dengan Kondisi Keuangan dan Preferensi Resiko Wajib Pajak Sebagai Variabel Moderating (Study Empiris pada Wajib Pajak Orang Pribadi di Kota Pekanbar - Prima Yuslina; Amries Rusli Tanjung; Alfiati Silfi (Akuntansi dan Manajemen, 2018)
This research aims to examine the effect of tax authorities, tax knowledge and taxpayer awareness on taxpayer compliance with financial conditions and taxpayer risk preferences as a moderating variable. The sample in this study is 100 individual taxpayers who conduct business activities and free work in Pekanbaru Distribution of questionnaires is done by proportional sampling method. The questionnaire distributed was 110, but only 100 could be processed with a response rate of 90.9%. The data analysis technique in this research uses the classic assumption test, and Moderated Regression Analysis (MRA) through SPSS 23. The results of the testing of the research hypothesis indicate that of the nine hypotheses in this study, there were only 2 hypotheses that were not proven, namely hypothesis 5, moderated tax knowledge financial conditions have an effect on taxpayer compliance and hypothesis 7, namely tax service providers moderated wp risk preferences affect taxpayer compliance. Meanwhile, 5 more hypotheses have proved to be influential.